2019
DOI: 10.3390/antiox8050138
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Anthocyanin Contents in Olives (cv Cellina di Nardò) during Ripening and after Fermentation

Abstract: The olive tree “Cellina di Nardò” (CdN) is one of the most widespread cultivars in Southern Italy, mainly grown in the Provinces of Lecce, Taranto, and Brindisi over a total of about 60,000 hectares. Although this cultivar is mainly used for oil production, the drupes are also suitable and potentially marketable as table olives. When used for this purpose, olives are harvested after complete maturation, which gives to them a naturally black color due to anthocyanin accumulation. This survey reports for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…As mentioned hydroxytyrosol is present in high concentration in olive oil which also contains other potent polyphenolic antioxidants such as oleuropein, tyrosol, coumaric acid, caffeic acid, vanillic acid, ferulic acid, kaempferol, and quercetin [10]. Aprile et al [11] assessed for the first time the antioxidant activity and the total polyphenolic content of olive fruits from the olive tree "Cellina di Nardò" (CdN), one of the most widespread cultivars in Southern Italy. The results showed that the fully maturation is the best harvest time to obtain a table olive with a high content in polyhpenols [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned hydroxytyrosol is present in high concentration in olive oil which also contains other potent polyphenolic antioxidants such as oleuropein, tyrosol, coumaric acid, caffeic acid, vanillic acid, ferulic acid, kaempferol, and quercetin [10]. Aprile et al [11] assessed for the first time the antioxidant activity and the total polyphenolic content of olive fruits from the olive tree "Cellina di Nardò" (CdN), one of the most widespread cultivars in Southern Italy. The results showed that the fully maturation is the best harvest time to obtain a table olive with a high content in polyhpenols [11].…”
mentioning
confidence: 99%
“…Aprile et al [11] assessed for the first time the antioxidant activity and the total polyphenolic content of olive fruits from the olive tree "Cellina di Nardò" (CdN), one of the most widespread cultivars in Southern Italy. The results showed that the fully maturation is the best harvest time to obtain a table olive with a high content in polyhpenols [11]. It was also shown that different treatments that are necessary to remove the bitterness of the raw olive and to stabilize them to obtain edible table olives, cause a loss in phenolic substances which also results in a loss of antioxidant activity [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between color and pigment content is well known in the literature [ 46 ]: the crushing of very green olives produces a typical green colored oil due to the high content in chlorophyll; if olives are more mature, carotenoids will prevail, determining a yellow-gold colored oil. Additionally, as the maturation progresses, the content and profile of phenolic compounds will also be affected: crushing green olives will result in an oil characterized by a higher content of phenolic acids, phenolic alcohols, oleuropein, and secoiridoids, whereas oils produced with dark brown olives will have a high content of anthocyanins, water-soluble plant pigments that take on different colors: red, blue, or violet [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This method could be applied, even in the case of non-volatile or thermolabile compounds. HPLC has been used to identify phenolic compounds and anthocyanins in grape skins [59], cornelian cherry fruit [60], Morus alba [61], olives [62], or açai [63].…”
Section: Introductionmentioning
confidence: 99%